Determining of vehicle capacity based on a lot size of goods - Limba, Rimantas; Fadina, Olga (Transport, 2004)
The size of lots of goods, vehicle type and capacity as well as the method of transportation should be properly matched. The coordination of these key parameters could reduce freight transportation costs. This can also help to save time. The proper choice of the type of a vehicle to carry the particular cargo could reduce the wear of transport facility and ensure freight safety on the road. The above measures would result in saving of resources.First Published Online: 27 Oct 2010